2019
DOI: 10.1111/jhn.12639
|View full text |Cite
|
Sign up to set email alerts
|

Association of meal and snack patterns with micronutrient intakes among Greek children and adolescents: data from the Hellenic National Nutrition and Health Survey

Abstract: Background The present study aimed to examine how different meal and snack patterns are associated with micronutrient intakes and diet quality among a nationally representative sample of Greek children and adolescents aged 1–19 years from the cross‐sectional Hellenic National Nutrition and Health Survey (n = 598). Methods Meal and snack patterns were derived using 24‐h dietary recalls. Mean adequacy ratio (MAR) was used as an overall measure of diet quality. Multiple linear regression adjusted for covariates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Work from younger paediatric populations and adults in the US suggest that snacks can help contribute to higher overall diet quality but snacking also clearly contributes to greater intake of food groups to limit including refined grains, added sugar, and fat (15,16,39,40) . This trend was also observed in an international sample of children and adolescents; greater snacking frequency was associated with higher micronutrient intakes, but the main sources of snack energy were desserts, sweets, and baked products (41) . Our work confirms these findings and further contributes important details about snacking characteristics and diet quality.…”
Section: Discussionsupporting
confidence: 60%
“…Work from younger paediatric populations and adults in the US suggest that snacks can help contribute to higher overall diet quality but snacking also clearly contributes to greater intake of food groups to limit including refined grains, added sugar, and fat (15,16,39,40) . This trend was also observed in an international sample of children and adolescents; greater snacking frequency was associated with higher micronutrient intakes, but the main sources of snack energy were desserts, sweets, and baked products (41) . Our work confirms these findings and further contributes important details about snacking characteristics and diet quality.…”
Section: Discussionsupporting
confidence: 60%
“…The above findings could be related to a possible postprandial hyperglycemia and lipemia [ 36 ]. Data from the cross-sectional Hellenic National Nutrition and Health Survey in 598 children and adolescents aged 4– 19 years, showed that increased snack consumption was positively correlated with vitamin D, vitamin K, riboflavin, niacin, pantothenic acid, folate, magnesium, copper and selenium intake [ 37 ]. A metanalysis of 47 studies who investigated the correlation between breakfast consumption and nutritional adequacy, body weight and academic performance in children and adolescents showed that the consumption of a healthy breakfast consisting of a variety of foods on a daily basis (particularly whole grains, rich with roughage and nutrients, fruit and dairy products) is beneficial for children’s health [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of understanding the nutrient intake profiles of dietary patterns [57], only a small number of studies have reported on the associations between the dietary patterns and nutrient intakes of children aged 2-5 years in high-resource countries [4,53,[58][59][60][61][62][63][64][65][66][67][68]. Of the diet quality studies published in English and focused on pre-school nutrient intakes, twelve have reported patterns associated with iron intakes (Table 2) [53,[58][59][60][61][62][63][64][65][66][67][68]. These studies have implemented a variety of approaches, including three that used PCA [53,58,64], they were from a variety of locations (South Korea, the Netherlands, UK, USA, Australia, and Greece), and they reported varied results.…”
Section: Dietary Patterns and Iron Intakes Of Pre-schoolersmentioning
confidence: 99%
“…Iron intake has been positively associated with pre-schooler diets characterised by healthier foods (such as fruit, fish, rice, and vegetables) [58,64], fruit juice [60], 'good' diets [61], and non-haem and non-iron fortified foods (such as cheese and bread) [53]. In addition, it has been inversely associated with patterns dominated by confectionery and convenience foods [58,59] and snack frequency [66]. For South Korean children, where cluster analysis identified two patterns for foods consumed outside of the home, the index of nutritional quality for iron was lower for a mixed pattern than for a rice-centred pattern [67].…”
Section: Dietary Patterns and Iron Intakes Of Pre-schoolersmentioning
confidence: 99%